Pertimbangan Hukum Dalam Mengabulkan Permohonan Wali Adhal Di Pengadilan Agama Sumbawa Besar: Analisis tentang Penetapan Nomor 135/Pdt.P/2021/PA.Sub - Anita Nabila Nurdiansari; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the legal considerations used by the judge in Determination Number 135/Pdt.P/2021/PA.Sub in granting the petition for wali adhal (the guardian who refuses to marry off his daughter), and the legal consequences of the guardian adhal determination. This research uses the normative method. The data analysis technique used in this research is qualitative data analysis. The results of this study showed that one of the judges' basic considerations in determining wali adhal was the refusal of the wali nasab (the guardian who has blood relation) to marry off the applicant with his prospective husband not based on law. The legal consequences arising from the wali adhal determination were the transfer of guardianship from the wali nasab to the guardian judge, namely the District Religious Affairs Office official as marriage registrar in their area.